2017
DOI: 10.2147/itt.s125429
|View full text |Cite
|
Sign up to set email alerts
|

FDA-approved immunosuppressants targeting staphylococcal superantigens: mechanisms and insights

Abstract: Immunostimulating staphylococcal enterotoxin B (SEB) and related superantigenic toxins cause diseases in human beings and laboratory animals by hyperactivating cells of the immune system. These protein toxins bind to the major histocompatibility complex class II (MHC II) molecules and specific Vβ regions of T-cell receptors (TCRs), resulting in the stimulation of both monocytes/macrophages and T lymphocytes. The bridging of TCR with MHC II molecules by superantigens triggers intracellular signaling cascades, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 141 publications
(237 reference statements)
0
2
0
Order By: Relevance
“…Monocytes also doubled by day 6 and continued to increase through day 22. Bacterial superantigens can upregulate TLR expression in primary human monocytes by ligation of MHC Class II [25].…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes also doubled by day 6 and continued to increase through day 22. Bacterial superantigens can upregulate TLR expression in primary human monocytes by ligation of MHC Class II [25].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 19 ] Rapamycin, which has mainly been used in the study of the pathogenesis and treatment of tumors and immune diseases, specifically inhibits the activity of mTOR. [ 20 21 ] Recent study has shown that rapamycin is a promising tool for the mechanistic study and treatment of pain. [ 22 ] In the present study, changes in behavior and protein expression related to the Akt/mTOR signaling pathway after the induction of neuropathic pain by oral administration of stavudine were investigated in mice.…”
Section: Discussionmentioning
confidence: 99%